Bacteriological Profile and Antimicrobial Susceptibility Patterns of Urine Culture Isolates from Patients in a Tertiary Care Centre in Lalitpur - Manandhar, Ruchee; Raghubanshi, Bijendra Raj; Mahato, Moni; Neupane, Sweekrity; Lama, Rajni (Birat Journal of Health Sciences, 2020)
Introduction: Urinary tract infection (UTI) is a microbial infection of the urinary system involving the urinary tract anywhere from kidney to urethra. It is one of the most common bacterial infections affecting men and women in developing countries with a high rate of morbidity and financial cost. Objectives: The objective of our study is to study the prevalence of UTI in patients attending KIST Medical College & Teaching Hospital (KISTMCTH), and determine the antimicrobial susceptibility pattern of bacteria thus isolated. Methodology: A total of 3742 urine samples from patients suspected of urinary tract infections presenting with the history and symptoms suggestive of urinary tract infection, attending various departments of KISTMCTH from April 2017 to April 2018 were studied. Isolates were identified by standard microbiological methods and tested for in vitro antibiotic susceptibility by modified Kirby-Bauer disc diffusion method. Results: Pathogenic bacteria were isolated from 646 out of 3742 urine samples (17.26%). Escherichia coli was the most common bacteria isolated (67.02%) followed by Klebsiella pneumoniae (14.5%). Other bacteria isolated were Enterococcus spp, Pseudomonas aeurigenosa, Klebsiella oxytoca, Proteus mirabilis, Satphylococcus aureus, Coagulase negative staphylococcus spp, Proteus vulgaris, Acinetobacter spp, Citrobacter freundii, Citrobacter diversus and Enterobacter spp. The isolated pathogenic bacterias were most resistant to Ampicillin (46.43%) and least resistant to Imipenem (6.03%). However, the first line antibiotic the bacterias were least resistant to was cefotaxime (7.12%). Conclusions: Marked resistance has been observed with commonly prescribed antibiotics like Ciprofloxacin and Norfloxacin. Therefore, studies should be conducted routinely to identify the common bacteria causing UTI and formulate appropriate antibiotic policy.